Pendidikan Multikultural Dalam Membangun Integrasi Nasional - Rejoice Leny Simatupang; Yonatan Alex Arifianto (Institut Agama Kristen negeri Kupang, 2022)
The many threats to national integration both from within and from outside must be immediately addressed by the government and also the Indonesian people. The problems that became one of the divisions were religious blasphemy and hate speech by several individuals who did not pay attention to and care about one group or another individual. The purpose of this paper is to find out the extent to which the government seeks national integration within the Indonesian state which is written using a qualitative descriptive method which is to describe the existing phenomenon and then describe it into a description, and which is the basis for writing this article and then begins by knowing the urgency of multicultural education as a barrier to the threat of national integration, then continues with the views of experts regarding the creation of harmonious national integration, its relationship with multicultural education, and ends by knowing what are the contributions of the Indonesian government in thwarting the existing threats. Then the result of this discussion is that it is known that the government seeks multicultural education in the fields of defense and security, politics, economy, and also socio-culture, because in carrying out their respective roles they must be based on a sense of tolerance, togetherness for the creation of Indonesian unity which has been fought for by the fighters. Indonesia's independence in 1945 and is also based on the ideology of Pancasila and Bhineka Tunggal Ika. With a sense of togetherness and tolerance among religious, ethnic, cultural, linguistic people, as well as various views and understandings of threats to the integration or national unity of Indonesia, it will not be a problem because of the formation of harmony in the life of the nation, state and language.